2022
DOI: 10.22521/edupij.2022.111.7
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship Practices and Research Productivity Among Early-Career Educational Psychologists in Universities

Abstract: Background/purpose -This study analyzed the contribution of three mentorship practices relatively and cumulatively to the research productivity of early-career academics in the field of educational psychology in universities. The study was conducted in the South-South region of Nigeria.Materials/methods -The research method adopted was the quantitative approach, following the ex-post facto research design. The study's population covered 723 early-career researchers (ECRs) in educational psychology distributed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The study concluded that university management should support the mentoring programme by formulating and implementing policies to curb the prevalence of the identified challenges. Okon et al (2022) investigated how cloning, nurturing, and apprenticeship practices impact the research productivity of early career academics in nineteen universities in the South-South region of Nigeria. Data collected from 644 respondents were statistically analysed using regression analysis and other descriptive statistics.…”
Section: 5mentioning
confidence: 99%
“…The study concluded that university management should support the mentoring programme by formulating and implementing policies to curb the prevalence of the identified challenges. Okon et al (2022) investigated how cloning, nurturing, and apprenticeship practices impact the research productivity of early career academics in nineteen universities in the South-South region of Nigeria. Data collected from 644 respondents were statistically analysed using regression analysis and other descriptive statistics.…”
Section: 5mentioning
confidence: 99%
“…The quality of teachers in any nation has a lot in common with the standard of education, and the standard of education shares a lot with the available learning opportunities for professional development. The emphasis on teachers" professionalism is affirmed by the National Planning Commission (NPC), ( 2004) that at least 80 percent of teachers at all levels of education in Nigeria should be professionals (Mohammed, 2014, Ukpor, Ashibi, Akpan, & Okon, 2014Okon & Ubi, 2021;Okon, Owan, & Owan, (2022), Obot, Apebende, Okon & Bekomson, 2020). The Teachers" Registration Council of Nigeria (TRCN) which was established by ACT 31 of 1993 now CAP T. 3 of 2004, in fulfillment of the quest for the professionalization of teaching has a vision of making teachers" quality match with international standards.…”
Section: Introductionmentioning
confidence: 99%
“…Research evaluation (RE) has recently emerged as a hot topic for academia [1]. This topicality stems from the great importance of RE to academic stakeholders, both internal and external [2], [3].…”
Section: Introductionmentioning
confidence: 99%
“…The review of Scopus/WoS literature on RE showed that researchers mainly focus on its positive effects [12], tools [13], country specificities [1], [4], [11] and research impact evaluation [6], [11], [12]. At the same time, researchers do not pay enough attention to the dark side of RE.…”
Section: Introductionmentioning
confidence: 99%